Factors Associated with Iron Supplementation During Pregnancy Among Married Women in Indonesia - Desy Imelda; Yuni Asri; Alfunnafi Fahrul Rizzal (Health Gate, 2026)
Background: Iron supplementation during pregnancy is an essential intervention to prevent maternal anemia and adverse pregnancy outcomes. However, disparities in iron supplementation coverage among pregnant women remain a public health concern in Indonesia. Several factors, including sociodemographic characteristics, media exposure, women’s autonomy, and antenatal care (ANC) utilization, may influence iron supplementation during pregnancy. Objective: This study aimed to analyze factors associated with iron supplementation during pregnancy among married women in Indonesia. Methods: This study employed a cross-sectional design using secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS) women’s dataset (IDIR71FL). The study included married women aged 15–49 years with complete information related to iron supplementation during pregnancy. Weighted analysis was applied before statistical analysis to account for the complex sampling design. Data were analyzed using IBM SPSS Statistics version 25. Descriptive statistics were presented as frequencies and percentages, while bivariate analysis was conducted using the chi-square test with a significance level of p<0.05. Results: The study found that sociodemographic characteristics, media exposure, women’s involvement in healthcare decision-making, and ANC visits were significantly associated with iron supplementation during pregnancy (p<0.001). Women with secondary education, better media exposure, greater autonomy in healthcare decision-making, and more than four ANC visits had higher proportions of iron supplementation receipt during pregnancy. ANC utilization showed the strongest association with iron supplementation coverage. Conclusion: Iron supplementation during pregnancy among married women in Indonesia was significantly influenced by demographic, socioeconomic, media exposure, and maternal healthcare factors. Strengthening ANC services, expanding maternal health education through mass media, and promoting women’s empowerment are important strategies to improve iron supplementation coverage and reduce maternal anemia in Indonesia.Keywords: iron supplementation; antenatal care; maternal health; media exposure; women’s autonomy